Implications of Foot Ulceration in Hemodialysis Patients: A 5-Year Observational Study - Hassan Al-Thani; Ayman El-Menyar; Valsa Koshy; Ahmed Hussein; Ahmed Sharaf; Mohammad Asim; Ahmed Sadek (Journal of Diabetes Research)
Foot ulceration (FU) remains a serious concern for patients worldwide. We analyzed the incidence, risk factors, and outcome of FU in hemodialysis (HD) patients. A retrospective cohort study was conducted for 252 HD patients who were followed up for 5 years. Patients were categorized according to whether they developed FU or not. The FU group (17%) was older and had significantly higher incidence of nephropathy, retinopathy, peripheral (PAD), coronary artery disease (CAD), and diabetes mellitus (DM) as compared to no-FU group. FU group had higher frequency of major amputation (P=0.001) and HD vascular access (P=0.01). Patients with combined DM and PAD had a 10-fold increased risk of FU in comparison to those who had DM alone. Presence of PAD was the main independent predictor for development of FU in HD with an adjusted odd ratio (aOR) of 16.0 (95% CI: 4.41–62.18; P=0.001). After adjusting for age, sex, and CAD, predictors for mortality were PAD (aOR 4.3), FU (aOR 3.6), and DM (aOR 2.6). FU is common in HD patients regardless of DM. However, the presence of PAD is significantly associated with more FU and mortality in HD. HD patients need intensive foot care and warrant progressive modification of vascular risk factors.